2018
DOI: 10.1016/j.bbamcr.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

4TM-TRPM8 channels are new gatekeepers of the ER-mitochondria Ca2+ transfer

Abstract: Calcium (Ca) release from the endoplasmic reticulum plays an important role in many cell-fate defining cellular processes. Traditionally, this Ca release was associated with the ER Ca release channels, inositol 1,4,5‑triphosphate receptor (IPR) and ryanodine receptor (RyR). Lately, however, other calcium conductances have been found to be intracellularly localized and to participate in cell fate regulation. Nonetheless, molecular identity and functional properties of the ER Ca release mechanisms associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Recently, a new family of TRPM8 channel isoforms as functional ER Ca 2+ release channels expressed in MAMs has been identified (Bidaux et al, 2018). We also confirmed that SR-resident TRPM8 participated in the regulation of cellular and mitochondrial Ca 2+ homeostasis in the VSMCs.…”
Section: Ca 2+ Transfersupporting
confidence: 70%
“…Recently, a new family of TRPM8 channel isoforms as functional ER Ca 2+ release channels expressed in MAMs has been identified (Bidaux et al, 2018). We also confirmed that SR-resident TRPM8 participated in the regulation of cellular and mitochondrial Ca 2+ homeostasis in the VSMCs.…”
Section: Ca 2+ Transfersupporting
confidence: 70%
“…2) They were performed in the absence of extracellular Ca 2+ in order to exclude an activation of P2X receptors by ATP and an influx of Ca 2+ that was reported to participate in glucose-mediated mitochondrial Ca 2+ rise (35). 3) We used ATP to stimulate ER-mitochondria Ca 2+ exchange in INS-1E cells, as classically performed in numerous cell types (17,27,29,(38)(39)(40). Moreover, ATP is a physiological extracellular signaling molecule of b-cells, arising from presynaptic terminals innervating the islets (as acetylcholine), from insulin secretion vesicles, or from connexin hemichannels and pannexin channels (41), and activation of P2YR was known to stimulate insulin secretion in a glucose-dependent manner (42).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor and TRPM8 in the ER membrane [94,95] by regulating tumour-stroma interaction [34,35]. Therefore it is important to clarify the effects of metabolic drugs on autophagy in tumours and to consider their association with autophagy inhibitors.…”
Section: Mitochondrial-associated Er Membranes (Mam)mentioning
confidence: 99%